Členitev slovenskega podeželja Prispevek k usmerjanju skladnega regionalnega razvoja - Kladnik, Drago; Ravbar, Marjan (Geografija Slovenije, 2003)
Monitoring the transformation of the Slovene countryside revealed that there are relatively heavily urbanized flatland and valley areas, and on the other, peripheral areas where depopulation and the disintegration of the cultural landscape are increasingly pronounced.For the evaluation of the countryside and its typological division, objective criteria are selected that reflect the natural conditions, the principal characteristics of agriculture, and the fundamental demographic, economic, functional, housing, infrastructural, and environmental conditions. Overall, the evaluation is based on the level of individual settlements which enables thorough spatial differentiation. A complex evaluation is carried out by establishing the value and representation of individual groups of parameters and their corresponding weights. On the basis of partial syntheses, two synthetic maps of developmental movements in the countryside are presented that provide a solid foundation in the effort to ensure harmonious regional development.